FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK KENDARAAN BERMOTOR (Studi Kasus Pada Kantor SAMSAT Serpong- Tangerang Selatan) - Shadrina, Ghina; Trisnawati, Estralita (Jurnal Paradigma Akuntansi, 2024)
The purpose of thissstudy is to empirically prove the effect of taxpayerrawareness, moral obligation, implementation of e-samsat, service quality and tax sanctions on taxpayer compliance in paying motor vehicle taxes at the Samsat Serpon office, South Tangerang. This study uses a survey method. through a questionnaire instrument to 100 respondents. The data processing in this study uses the Statistical Product and Service Solution program for Windows version 25 (SPSS version 25) and Microsoft Excel 2010. The results obtained from the study show that moral obligations, implementation of e-samsat, service quality and tax sanctionsshave a significant influence. on taxpayerrcompliance in paying motorrvehicle taxes, while taxpayer awareness does not have a significant effect on taxpayer compliance in paying motor vehicle taxes.